2016
DOI: 10.1007/s12311-016-0764-2
|View full text |Cite
|
Sign up to set email alerts
|

High Hypnotizability Impairs the Cerebellar Control of Pain

Abstract: In the general population, transcranial anodal direct current stimulation of the cerebellum (ctDCS) reduces pain intensity and the amplitude of nociceptive laser evoked potentials (LEPs), whereas cathodal ctDCS elicits opposite effects. Since behavioral findings suggest that the cerebellar activity of highly hypnotizable individuals (highs) differs from the general population, we investigated whether hypnotizability-related differences occur in the modulation of pain by ctDCS. Sixteen healthy highs (according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Indeed, the vestibular and neck proprioceptive information are conveyed to the frontoparietal, insular, and cingulate cortices which show also hypnotizability-related morphofunctional properties (Landry et al, 2017). In addition, cerebellar function, which is related to hypnotizability (Bocci et al, 2017), is required for the elaboration of sensorimotor information related to the head position (Manzoni, 2005;Kammermeier, Kleine, & Büttner, 2009). Spectral analysis of EEG signals can be used to characterize the cortical representation of the head posture.…”
Section: Sensorimotor Integration and Hypnotizabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the vestibular and neck proprioceptive information are conveyed to the frontoparietal, insular, and cingulate cortices which show also hypnotizability-related morphofunctional properties (Landry et al, 2017). In addition, cerebellar function, which is related to hypnotizability (Bocci et al, 2017), is required for the elaboration of sensorimotor information related to the head position (Manzoni, 2005;Kammermeier, Kleine, & Büttner, 2009). Spectral analysis of EEG signals can be used to characterize the cortical representation of the head posture.…”
Section: Sensorimotor Integration and Hypnotizabilitymentioning
confidence: 99%
“…Alterations of visual and leg proprioceptive information (Santarcangelo, Scattina, Carli, Macerata, & Manzoni, ) and asymmetric tactile feet stimulation (Solari, Orsini, & Santarcangelo, ) induce larger and/or faster body sway in highly hypnotizable individuals ( highs ), while tonic neck rotation induces changes in the velocity of body sway only in low hypnotizable subjects ( lows ) (Santarcangelo et al., ). Hypnotizability is also associated with morphofunctional differences in the cerebral cortex (Landry, Lifshitz, & Raz, ) and cerebellar cortex (Picerni et al., ; Bocci et al., ), which are structures relevant to sensorimotor integration. Indeed, the vestibular and neck proprioceptive information are conveyed to the frontoparietal, insular, and cingulate cortices which show also hypnotizability‐related morphofunctional properties (Landry et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The highs do not exhibit learning effects due to task repetition in both postural and visuomotor tasks [2]. In contrast to the general population, reports showed increased pain perception associated with increased amplitude of cortically evoked nociceptive potentials during transcranial anodal cerebellar stimulation in highs [15]. The structural variations in the salience network, particularly in the insula, may be responsible for higher emotional intensity during imagery [16], recall of emotional events [17], and perception of the inner world and sensitivity/empathy in highs than that in lows [18].…”
Section: Hypnotizability As a Psychophysiological Traitmentioning
confidence: 99%
“…Also, it has been shown that highs receiving nociceptive stimulation after anodal cerebellar stimulation report paradoxically increased pain intensity associated with increased amplitude of the cortically evoked potentials [13], in contrast to a sample of lows and medium hypnotizable participants (mediums). Finally, reduced cerebellar inhibition of the cerebral cortex has been suggested as one of the possible factors responsible for facilitating ideomotor responses to sensorimotor suggestions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%